IDENTIFYING FACTORS THAT AFFECT CONSUMER SATISFACTION OF PARKLATZ CAFÃ© IN PONOROGO CITY, EAST JAVA, INDONESIA: AN APPLICATION OF EXPLORATORY FACTOR ANALYSIS - Susilo, Adib (Falah: Jurnal Ekonomi Syariah, 2020)
This study aims to find out how the exploratory factor analysis (EFA) conducted which can be used in further research. Also to find out how the factors need to be grouping and then confirmed to assess the degree to which the data meet the expected structure. The author has conducted a survey of 124 respondents. The respondents were asked to give their responses on a five-point Likert scale through a questionnaire. The data has been analyzed with exploratory factor analysis (EFA) using Varimax rotation, which reduced the data into several factors. The findings of this study indicate that product, service satisfaction, price satisfaction, promotion, and customer hospitality influence customer satisfaction of Parklatz Café in Ponorogo City.